2014
DOI: 10.1002/ejlt.201300489
|View full text |Cite
|
Sign up to set email alerts
|

Cationic derivative of polyprenol, a potential component of liposomal drug carriers, does not alter renal function in rats

Abstract: Potential toxicity of a cationic derivative of polyprenol (APren-7) with lipofecting activity was examined, especially its influence on renal haemodynamics and function, in order to conduct further investigation of its suitability as a component of liposomal drug carriers. Sprague-Dawley rats received daily injections (0.5 mL, s.c.) of liposomes comprised of 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) and APren-7 (LP); classic liposomes composed of DOPE only (L); water solvent (W). After 4 weeks rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Analytically speaking, the most thoroughly studied isoprenoid structures seem to be those extracted from Ginkgo biloba [34] plausibly due to plant's high popularity in the Eastern traditional medicine. Apart from that, there are several studies that examine polyisoprenoid-containing bilayer lipid membrane models [35][36][37] and liposomal formulations [38]. All the accumulated research notwithstanding, there are still only a few commercial polyprenol formulations such as Ropren ® [39], Fortepren ® [3], and antiviral polyprenol aerosol [40] available on the market today, and thus we wished to explore the potential of such polyprenol preparations further.…”
Section: Discussionmentioning
confidence: 99%
“…Analytically speaking, the most thoroughly studied isoprenoid structures seem to be those extracted from Ginkgo biloba [34] plausibly due to plant's high popularity in the Eastern traditional medicine. Apart from that, there are several studies that examine polyisoprenoid-containing bilayer lipid membrane models [35][36][37] and liposomal formulations [38]. All the accumulated research notwithstanding, there are still only a few commercial polyprenol formulations such as Ropren ® [39], Fortepren ® [3], and antiviral polyprenol aerosol [40] available on the market today, and thus we wished to explore the potential of such polyprenol preparations further.…”
Section: Discussionmentioning
confidence: 99%
“…Worth noting is the protective effect of DOPE, used as the component of the transfection mixture, on cell proliferation. Moreover, Gawrys et al [ 15 , 16 ] showed in in vivo experiments, that AP-7/DOPE liposomes did not affect, after subcutaneous administration, the overall condition, behaviour nor the function of the cardiovascular and renal excretory system of rats. Though in our cell-line studies AP-7 influenced B16-F10 cell proliferation, it seems that this compound and hopefully other Amino-Prenols too, are non-toxic for living organisms and can be used in various applications.…”
Section: Discussionmentioning
confidence: 99%
“…As a result good efficacy of in vitro transfection with application of AP-7-based (aminoprenol composed of seven isoprene units) complexes has been demonstrated [ 10 ]. Further studies on AP-7 as a drug carrier in rats revealed liposomes containing AP-7 to be harmless to the experimental animals [ 15 ]. AP-7 containing liposomes did not affect functions of the excretory and cardiovascular systems, nor renal morphology [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In acute experiments rats were anesthetized with intraperitoneal (ip) sodium thiopental (100 mg/kg; Sandoz GmbH, Kundl, Austria), which provided stable anesthesia for about 4 h. All surgical preparations were already described in detail (Gawrys et al, 2014;Badzynska et al, 2020). Throughout the experiment the temperature of the animal was kept constant (37°C).…”
Section: Acute Infusion Of Chymostatin To Anesthetized Rats (I)mentioning
confidence: 99%